CRITIQUE OF IDEOLOGY BIN GEORGE ORWELL’S NOVEL 1984: A HANS-GEORG GADAMER’S HERMENEUTICS READING - Fajri, Daniel Ahmad; Noverino, Romel (Universitas Gunadarma, 2019)
This study is to analyze George Orwell’s novel 1984 that published in 1949. This study uses descriptive qualitative method. The analysis of this undergraduate thesis focuses on hermeneutical reading of the text. This study aims to find out critique of ideology concept by reading both the text and the researcher (as interpreter) horizons to get a current meaning of the text. This study applies philosophical hermeneutics of Hans-Georg Gadamer and Jurgen Habermas’s critical theory to analyze the novel. After interprets the horizon of the text with three stages of analysis (understanding, historical consciousness, and history of effect), then the prejudice/presupposition (Habermas’ critique of ideology) appear dialectically as interpreter horizon to read the 1984 in its current context. The result proves that, although the work of structure of power in Orwell's life and interpreter are different - Orwell who live in the tension of world ideologies (with fascism, soviet communism, and other totalitarian power) and interpreter in the late-capitalism era (with liberal consensus domination), but analysis of critique of ideology in the 1984 novel in the current context relates to several things. Among other things are, total domination of the system like distorting symbolic interactions and how power works supported - manifested in high-level technology with its propaganda and supervision of civil society. At this point, to resist against totalitarian system, both Orwell and Habermas are similar as well - a process of rationalization with a communication paradigm with emancipatory mission to give a progressive free individual formation in the society.